Exploring Layered Ruddlesden-Popper Structures for High-Performance Energy Devices - Ahmad Hussain; Sumaira Zafar; Nawishta Jabeen; Muhammad Usman Khan; Imtiaz Ahmad Khan; Mahmoud M. Hessien (Inorganics, 2025)
This study presents comprehensive DFT calculations to determine the structural, electronic, mechanical, and optical properties of the Ruddlesden–Popper Phase family member, La2XO4, which has an orthorhombic crystal structure with a Cmce space group. Ultrasoft pseudopotential plane wave and PBE-GGA approaches have been implemented using the CASTEP tool. The exchange–correlation approximation calculations show that the La2XO4 (where X = Ni, Fe, Ba, and Pb) compounds possess no band gap. The results indicate that the compounds are metallic, which are ideal for supercapacitor (SC) applications. The compound’s optical conductivity, dielectric function, extinction coefficients, absorption refractive index, loss function, and reflectivity are also analyzed for SC applications. UV spectra of the compounds observed high absorption coefficient (105 cm−1), dielectric function (9–10), optical conductivity (7 fs−1), and refractive index (4) values. Furthermore, as B/G > 1.75, the mechanical (elastic) properties have shown ductile behavior and mechanical stability. Using the Born stability criteria, the mechanical stability of the compounds is examined. All of the compounds are ductile, according to Pugh’s and Frantesvich ratios. Finally, time-simulations-dependent temperature stability plots for the compounds are computed by employing dynamical stability with norm-conserved pseudopotential, which confirm their potential for SC applications.